El cultivo de la yuca en Bolivia - Lennis, J.; Alvarado, A. (International Center for Tropical Agriculture, 1991)
In Bolivia cassava is grown in 4 large areas, Beni-Pando, Yungas, Santa Cruz, and Chapare, where soils are mostly Inceptisols with some Entisols in the lowlands; Ultisols and Inceptisols predominate in the Yungas area. Currently 47,000 ha are planted to cassava in the country, with av. yields of 14.2 t/ha. The crop is monocropped mainly in the regions of Beni-Pando and Santa Cruz and associated with other crops, particularly coca, in the regions of Yungas and Chapare. Most of the cassava is consumed locally in the form of fresh roots; the use of this crop in animal nutrition is min. Main production constraints are the use of low yielding var., deficient technical assistance, and attack by rodents. Research on the crop is carried out by the Instituto Boliviano de Tecnologia Agropecuaria, at 2 of its exptl. stations (Sapecho and La Jota), and by the Instituto de Investigaciones Agricolas El Vallecito; emphasis has been placed on plant breeding regarding the collection and assessment of local genetic materials and the introduction of CIAT genetic material. Greater institutional coordination, improved facilities for international germplasm exchange, regional var. trials, and training of research personnel are required. (CIAT)